Postbuckling behavior of saddle loaded shell - Středová, Doubravka; Tomek, Petr (Univerzita Pardubice, 2008)
This article deals with the loss of stability of the cylindrical shell subjected to a punch of the stiff body - supporting saddle. It also compares post-buckling behavior of the real experimental cylindrical shell with the numerical model. The numerical model together with the saddle is created as one body. The resulting loading curves of both the real model and the computational model are in a relatively good accord. The differences will be studied within a future research where the emphases will be put on the initial impertections.
Pokritické chování radiálně zatížené válcové skořepiny
Nachkritisches Verhaltung die zylindrische Schale